2015
DOI: 10.1111/jpi.12271
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses activation of hepatic stellate cells through RORα‐mediated inhibition of 5‐lipoxygenase

Abstract: Liver fibrosis is scar tissue resulting from an uncontrolled wound-healing process in response to chronic liver injury. Liver damage generates an inflammatory reaction that activates hepatic stellate cells (HSC) that transdifferentiate from quiescent cells that control retinol metabolism to proliferative and migratory myofibroblasts that produce excessive amounts of extracellular matrix proteins, in particular collagen 1a1 (COL1A1). Although liver fibrosis is reversible, no effective drug therapy is available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 58 publications
1
38
0
1
Order By: Relevance
“…5-LOX inhibitors have been shown to increase the activation of cultured hepatic cells and increase Kupffer cell apoptosis [49, 50]. The treatment with the COX inhibitor celecoxib results in a significant reduction in fibrosis in rat models [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…5-LOX inhibitors have been shown to increase the activation of cultured hepatic cells and increase Kupffer cell apoptosis [49, 50]. The treatment with the COX inhibitor celecoxib results in a significant reduction in fibrosis in rat models [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that melatonin might be developed into a promising treatment for liver fibrosis. In addition, some studies demonstrated that melatonin attenuated liver fibrosis via limiting the expression of profibrogenic genes [143], directly suppressing hepatic stellate cells activation [144], and so on.…”
Section: Protective Effects Of Melatonin On Liver Fibrosismentioning
confidence: 99%
“…Hepatic fibrosis is the wound‐healing process in response to chronic liver injury . Hepatic stellate cell (HSC) constitutes the accumulation of extracellular matrix (ECM) once they activated . The activated HSC expresses a variety of factors such as transforming growth factor‐β1 (TGF‐β1), which stimulate the HSC activation, and secrete collagens and smooth muscle α‐action (α‐SMA) .…”
Section: Introductionmentioning
confidence: 99%